Bilateral Bulky Adrenal Plasmacytomas with Very Good Response to Daratumumab-Based Therapy - Fang-Yu Wang; Han-Kuang Hsieh; Tso-Fu Wang; Yi-Feng Wu (Journal of Cancer Research and Practice)
Extramedullary myeloma disease represents an infrequent but aggressive variant of multiple myeloma (MM), and it is associated with a poor prognosis. An optimal treatment strategy for this clinical subset has not yet been clarified. In this report, we demonstrate a patient with MM with the uncommon manifestation of plasmacytomas with a very high burden in the bilateral adrenal glands at diagnosis, which were treated successfully with daratumumab-based second-line therapy.